STUDENTS’ SPEAKING PROBLEMS IN ENGLISH PRESENTATION - Susilawati, Meli Arya; Supardi, Iwan; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstrack: This research focuses on the students’ speaking problems in presentation of sixth semester students of English Education Study Program of Teacher Training and Education faculty, Tanjungpura University in academic year 2015/2016 both linguistic and nonlinguistic problems. The purpose of this research is to find out the most dominant and least problem faced by the sixth semester students in their presentation. This research used Descriptive method. The population of this research is sixth semester students of English education study program of Teacher Training and Education Faculty,Tanjungpura University class A and B. Sample taken from class A involved 38 students. The writer used questionnaire as the tools of data collection. The finding showed that the most dominant problem faced by the students in doing the presentation is vocabulary (18.94%), and the least problem in doing the presentation is fear of making mistake (15%). The other problems are lack of confident (17.23%), grammar (16.57%), and pronunciation (15.52%). Keyword: Speaking Problems, Linguistic Problems, Nonlinguistic Problems, Presentation. Abstrak: Fokus penelitian ini adalah untuk mengetahui masalah berbicara pada mahasiswa semester enam jurusan Bahasa Inggris FKIP Untan tahun ajaran 2015/2016. Masalah berbicara yang dimaksudkan termasuk masalah linguistik dan non linguistik. Penelitian ini bertujuan untuk mencari tahu masalah yang paling sering (dominan) dan yang paling sedikit dihadapi oleh mahasiswa semester enam saat presentasi. Penelitian ini menggunakan metode deskriptif. Populasi diambil dari mahasiswa semester enam jurusan bahasa Inggris FKIP Untan kelas A dan B. Sampel diambil dari kelas A sebanyak 38 orang. Penulis menggunakan questioner sebagai alat pengumpul data. Hasil pebelitian menunjukan bahwa masalah yang paling sering dihadapi oleh mahasiswa selama presentasi adalah masalah kosakata (18, 94%), dan masalah yang paling sedikit dihadapi mahasiswa selama presentasi adalah takut membuat kesalahan (15%). Masalah lain yang dihadapi mahasiswa selama presentasi yaitu kurang percaya diri (17,23%), tata bahasa (16, 95%) dan pengucapan (15, 52%). Kata Kunci: Masalah Berbicara, Masalah Linguistik, Masalah Nonlinguistik, Presentasi.